Selective delivery of IFN‐γ to renal interstitial myofibroblasts: a novel strategy for the treatment of renal fibrosis. Issue 3 (2nd December 2014) - Poosti, Fariba; Bansal, Ruchi; Yazdani, Saleh; Prakash, Jai; Post, Eduard; Klok, Pieter; van den Born, Jacob; de Borst, Martin H.; van Goor, Harry; Poelstra, Klaas; Hillebrands, Jan‐Luuk
Abstract : Renal fibrosis leads to end‐stage renal disease demanding renal replacement therapy because no adequate treatment exists. IFN‐γ is an antifibrotic cytokine that may attenuate renal fibrosis. Systemically administered IFN‐γ causes side effects that may be prevented by specific drug targeting. Interstitial myofibroblasts are the effector cells in renal fibrogenesis. Here, we tested the hypothesis that cell‐specific delivery of IFN‐γ to platelet‐derived growth factor receptor β (PDGFRβ)‐expressing myofibroblasts attenuates fibrosis in an obstructive nephropathy [unilateral ureteral obstruction (UUO)] mouse model. PEGylated IFN‐γ conjugated to PDGFRβ‐recognizing peptide [(PPB)‐polyethylene glycol (PEG)‐IFN‐γ] was tested in vitro and in vivo for antifibrotic properties and compared with free IFN‐γ. PDGFRβ expression was >3‐fold increased ( P < 0.05) in mouse fibrotic UUO kidneys and colocalized with α‐smooth muscle actin‐positive (SMA + ) myofibroblasts. In vitro, PPB‐PEG‐IFN‐γ significantly inhibited col1a1, col1a2, and α‐SMA mRNA expression in TGF‐β‐activated NIH3T3 fibroblasts ( P < 0.05). In vivo, PPB‐PEG‐IFN‐γ specifically accumulated in PDGFRβ‐positive myofibroblasts. PPB‐PEG‐IFN‐γ treatment significantly reduced renal collagen I, fibronectin, and α‐SMA mRNA and protein expression. Compared with vehicle treatment, PPB‐PEG‐IFN‐γ preserved tubular morphology, reduced interstitial T‐cell infiltration, and attenuated lymphangiogenesis (all P < 0.05) without affecting peritubular capillary density. PPB‐PEGIFN‐γ reduced IFN‐γ‐related side effects as manifested by reduced major histocompatibility complex class II expression in brain tissue ( P < 0.05 vs. free IFN‐γ). Our findings demonstrate that specific targeting of IFN‐γ to PDGFRβ‐expressing myofibroblasts attenuates renal fibrosis and reduces systemic adverse effects.—Poosti, F., Bansal, R., Yazdani, S., Prakash, J., Post, E., Klok, P., vanden Born J. deBorst M.H. vanGoor H. Poelstra K. Hillebrands, J.‐L. Selective delivery of IFN‐γ to renal interstitial myofibroblasts: a novel strategy for the treatment of renal fibrosis. FASEB J. 29, 1029–1042 (2015). www.fasebj.org